Repeated fed-batch cultivation of nitrogen-fixing bacterium, Bacillus sphaericus UPMB10, using glycerol as the carbon source - Ariff, Arbakariya; Ooi, Tze Chean; Mohd Saud, Halimi; Shamsuddin, Zulkifli (Universiti Putra Malaysia Press, 2010)
The exponential fed-batch cultivation of Bacillus sphaericus UPMB10 in 2 l stirred tank fermenter was performed by feeding the initial batch culture with 14 g l-1 of glycerol according to the algorithm aimed at controlling the specific growth rate (µ) of the bacterium. Very high viable cell count (1.14 x 1010 cfu ml-1), which was four times higher as compared to batch cultivation, was achieved in the fed-batch with a controlled µ at 0.4 h-1. In repeated exponential fed-batch cultivation, consisting of four cycles of harvesting and recharging, a final cell concentration of 1.9 x 1011 cfu ml-1 was obtained at the end of the fourth cycle (46 h). Meanwhile, acetylene reduction of cell samples collected from repeated fed-batch cultivation remained unchanged and was maintained at around 20 nmol C2H2 h-1 ml-1 after prolonged cultivation period, and was comparable to those obtained in batch and exponential fed-batch cultivation. Glycerol could be used as a carbon source for high performance cultivation of B. Sphaericus, a nitrogen fixing bacterium, in repeated fed-batch cultivation with high cell yield and cell productivity. The productivity (0.68 g l-1 h-1) for repeated fed-batch cultivation increased about 6 times compared to that obtained in conventional batch cultivation (0.11 g l1 h-1). A innovative method in utilizing glycerol for efficient cultivation of nitrogen fixing bacterium could be beneficial to get more understanding and reference in manipulating the integrated plans for sustainable and profitable biodiesel industry.